DETERMINANTS OF ISLAMIC BANKING ADOPTION: A COMPARATIVE STUDY OF CUSTOMER INTEREST IN INDONESIA AND MALAYSIA - Mohd Fazlon Bin Abdul Rahim; Hendri Mauliansyah (GREET, 2026)
This study investigates the determinants of Islamic banking adoption through a comparative analysis of customer interest in Indonesia and Malaysia, two leading Islamic finance markets characterized by contrasting levels of institutional development. Grounded in an integrated framework combining the Technology Acceptance Model (TAM) and Diffusion of Innovations Theory, this research employs a robust mixed-methods design, utilizing survey data from 1,000 respondents alongside qualitative insights to capture both behavioral trends and contextual nuances. The findings indicate that adoption is driven by a multidimensional interplay of religiosity, financial literacy, perceived benefits, service quality, social influence, institutional trust, and technological readiness, with significant cross-country variations. In Indonesia, adoption is predominantly shaped by religious commitment and ethical alignment, yet constrained by limited financial literacy and market awareness. In contrast, Malaysian customers exhibit stronger responsiveness to product innovation, digital integration, and social influence, reflecting a more mature Islamic banking ecosystem. The study’s key novelty lies in its integrative cross-country framework, which moves beyond single-factor explanations by demonstrating how cognitive, socio-cultural, and institutional determinants interact dynamically across different market contexts. By bridging micro-level behavioral theories with macro-level institutional differences, this research offers a more comprehensive explanatory model of Islamic banking adoption. The findings provide actionable insights for policymakers and financial institutions to design context-specific strategies that enhance customer engagement, strengthen financial inclusion, and accelerate the sustainable development of Islamic finance globally.